Enhancement of Power Quality by an Application FACTS Devices - Prashant Kumar (Institute of Advanced Engineering and Science, 2015)
The paper narrates widespread use of electrical energy by modern civilization has necessitated producing bulk electrical energy economically and efficiently. The Flexible AC Transmission system (FACTS) is a new technology based on power electronics, which offers an opportunity to enhance controllability, stability, and power transfer capability of AC transmission systems. Here SVC has been developed with the combination of TCSC and TCR. The paper contains simulation models of Thyristor controlled Series Capacitor (TCSC) and Thyristor controlled Reactor (TCR)-based Static VAR Compensator (SVC) which are the series and shunt Flexible AC Transmission Systems (FACTS) devices. The fact devices are designed by considering the line losses and their stability. The design and simulations of TCSC and TCR-based SVC shows the effectiveness of result using the MATLAB/Simulink. The designed system will try to reduce the voltage drops and electrical losses in the network without the possibility of transient especially in case of long transmission system. Student feedback indicates that this package is user-friendly and considerably effective for students and researchers to study theory of controlled reactor compensators, series capacitor compensator, and the reactive power control and voltage regulation.